2012
DOI: 10.1111/j.1558-5646.2012.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence Is Decoupled From Ecological Diversification in the Hawaiian Nesosydne Planthoppers

Abstract: Adaptive radiation involves ecological shifts coupled with isolation of gene pools. However, we know little about what drives the initial stages of divergence. We study a system in which ecological diversification is found within a chronologically well-defined geological matrix to provide insight into this enigmatic phase of radiation. We tested the hypothesis that a period of geographic isolation precedes ecological specialization in an adaptive radiation of host-specialized Hawaiian planthoppers. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 80 publications
(88 reference statements)
1
23
0
Order By: Relevance
“…Our estimate of the number of ecology driven speciation events is similar to the finding of Nyman et al [32] on sawflies (Hymenoptera: Tenthredinidae), and the conclusions from a broad literature survey of macroevolutionnary studies by Winkler & Mitter [98] that both suggest that the ratio of ecological versus non-ecological speciation in phytophagous insect is at the most “1:1”. This also echoes the results of Imada et al [99] on a group of 25 phytophagous moth species showing that none of them have speciated via ecological speciation and a study by Roesch Goodman et al [100] that demonstrates that geography and not ecology is responsible for the diversification of host specific Hawaiian plant hoppers. Furthermore, as underlined by previous authors [31,35], showing that a shift in ecological resource has accompanied a speciation event does not mean that ecological differentiation has triggered the formation of two species.…”
Section: Discussionsupporting
confidence: 87%
“…Our estimate of the number of ecology driven speciation events is similar to the finding of Nyman et al [32] on sawflies (Hymenoptera: Tenthredinidae), and the conclusions from a broad literature survey of macroevolutionnary studies by Winkler & Mitter [98] that both suggest that the ratio of ecological versus non-ecological speciation in phytophagous insect is at the most “1:1”. This also echoes the results of Imada et al [99] on a group of 25 phytophagous moth species showing that none of them have speciated via ecological speciation and a study by Roesch Goodman et al [100] that demonstrates that geography and not ecology is responsible for the diversification of host specific Hawaiian plant hoppers. Furthermore, as underlined by previous authors [31,35], showing that a shift in ecological resource has accompanied a speciation event does not mean that ecological differentiation has triggered the formation of two species.…”
Section: Discussionsupporting
confidence: 87%
“…This rate is nearly four times higher than the commonly used 'standard' rate of evolution for CO1 in insects, 2.3% per Myr 17 . Generally, divergence rates for CO1 fall within the range of 0.5-4% per Myr 18 , although Roesch Goodman et al 19 compiled a wider range of rates (1.3-10.6% per Myr) for divergences between sister species in a diversity of Hawaiian arthropod groups. Our high mean rate of evolution in CO1 compared with other studies either implies a faster rate of mutation in CO1 in Hyposmocoma or suggests that our age estimates are underestimates.…”
Section: Resultsmentioning
confidence: 99%
“…These comparative divergences suggest Swezeyana and Hevaheva may be marginally older genera that established earlier in the Hawaiian Islands. Mitochondrial rates of divergence vary across different organismal lineages, even among insects (Shapiro et al 2006, Magnacca and Danforth 2007, Goodman et al 2012, Haines et al 2014), and rate heterogeneity has been reported within psyllid lineages (e.g. Percy et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Wessel et al 2013). One factor that likely plays an important role in promoting species complexes is the instability and fluctuation in the geological landscape on Hawaii, with ongoing volcanic activity and shifting habitats (Goodman et al 2012). What Futuyma (2010) calls “ephemeral divergence”, where localized spatial and temporal divergence may be relatively short lived and unstable population structure prevents longer term adaptive signatures becoming established, could be contributing to the disruption of species boundaries and/or maintenance of within species complexes (e.g.…”
Section: Discussionmentioning
confidence: 99%